Developing Process Skills in Environment Studies - Dabas, Manisha Wadhwa nee Dabas (THE PRIMARY TEACHER, 2018)
Environmental Studies (EVS) at the primary stage is understood as “an integrated approach to science, social science and environment education” (NCERT, 2005). The subject is taught by exposing children to real-life situations, by which they make sense of the natural, physical, social and cultural environment around them. It is focused not only on concept formation but also on the development of process skills